The celebration of death in contemporary culture - Khapaeva, Dina (University of Michigan Press, 2017)
"The Celebration of Death in Contemporary Culture investigates the emergence and meaning of the cult of death. Over the last three decades, Halloween has grown to rival Christmas in its popularity and profitability; dark tourism has emerged as a rapidly expanding industry; and funerals have become less traditional. "Corpse chic" and "skull style" have entered mainstream fashion, while elements of gothic, horror, torture porn, and slasher movies have streamed into more conventional genres. Monsters have become pop culture heroes: vampires, zombies, and serial killers now appeal broadly to audiences of all ages. This book considers, for the first time, these phenomena as aspects of a single movement, documenting its development in contemporary Western culture. Previous considerations of our fixation on death have not developed a convincing theory linking the mounting demand for images of violent death and the dramatic changes in death-related social rituals and practices. This book offers a conceptual framework that connects the observations of the simulated world of fiction and movies--including The Twilight Saga, The Vampire Diaries, Night Watch, Hannibal, and the Harry Potter series--to social and cultural practices, providing an analysis of the specific aesthetics and the intellectual and historical conditions that triggered the cult of death. It also considers the celebration of death in the context of a longstanding critique of humanism and investigates the role played by 20th-century French theory, as well as by posthumanism, transhumanism, and the animal rights movement, in the formation of the current antihumanist atmosphere. With its critique of movie and book blockbusters and the death-related social rituals, festivals, and fashions that have coalesced into the cult of death, this timely volume will appeal to anyone hoping to better understand a defining phenomenon of our age. Scholars and general readers of cultural studies, film and literary studies, anthropology, and American and Russian studies will find this book thought-provoking"--